Comparative Study Between the Effects of Kinesio Taping and Pressure Garment on Secondary Upper Extremity Lymphedema and Quality of Life Following Mastectomy: A Randomized Controlled Trial - Sayed A. Tantawy PhD; Walid K. Abdelbasset PhD; Gopal Nambi PhD; Dalia M. Kamel PhD (Integrative Cancer Therapies, 2019)
Background: Breast cancer stands out among the most widely recognized forms of cancer among women. It has been observed that upper extremity lymphedema is one of the most risky and prevalent complication following breast cancer surgery that prompts functional impairment, psychological, and social problems. Purpose: To compare the effects of Kinesio taping and the application of the pressure garment on secondary lymphedema of the upper extremity. Methods: 66 women were randomly allocated to the Kinesio taping (KT) group (n=33) and pressure garment (PG) group (n=33). The KT group received Kinesio taping application (2 times per week for 3 weeks), while the PG group received pressure garment (20- 60 mmHg) for at least 15-18 hours per day for 3 weeks. The outcome measures were limb circumference, Shoulder Pain and Disability Index questionnaire (SPADI), hand grip strength, and quality of life at the baseline and end of intervention. Results: The sum of limb circumferences, SPADI, hand grip strength, and quality of life significantly improved after treatment in the KT group (P<0.05). While the PG group showed no significant improvement in SPADI, hand grip strength, physical, role, pain, and fatigue score p>0.05, while the sum of limb circumferences significantly decreased (P<0.05). Significant differences were observed between the KT and PG groups at the end of the intervention (P<0.05). Conclusion: KT had significant changes in limb circumference, SPADI, hand grip strength and overall quality of life than PG in the treatment of subjects diagnosed with lymphedema after mastectomy.